Screening for ligninase-producing bacteria from South East Pahang peat swamp forest soil - Mohamad Roslan, Muhamad Aidilfitri; Zainal Abidin, Zaima Azira; Mohd Omar, Suhaila (Malaysian Society for Microbiology, 2015)
Research on lignin degradation capability is previously restricted exclusively to fungi’s enzymes. However, recent studies revealed ranges of soil bacteria that able to produce ligninolytic enzymes. In fact, bacterial enzyme has some advantages over fungal enzymes such as in aspects of thermostability, acidic stability and mediator dependency. The present study concentrates on isolation and screening of ligninase-producing bacteria from South East Pahang Peat Swamp Forest (SEPPSF) soil using agar-based assay. Thirteen morphologically distinctive isolates were selected and able to show decolourization zone on Azure B plates. The ratio of decolourization zones were measured to the ratio of the colony size. Only four of the thirteen isolates were able to grow on lignin plates. Subsequently, they were tested on M1 agar supplemented with ligninolytic enzyme indicator compounds which were tannic acid (TA), guaiacol and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS). All four isolates showed growth on TA plates. Intense brown colour formation was observed around the colony of isolates AR3 and AR10 on guaiacol plates while none exhibited green coloration around the colonies when tested on ABTS plates. 16S rRNA gene sequencing and analysis indicated AR3, AR8 and AR13 as Burkholderia sp. while AR10 as Serratia sp. Based on the agar-based screening results, AR10 was perceived as potential ligninase-producing bacteria. More experiments would be conducted in the future to characterize AR10 and the ligninolytic enzymes produced.